Amorphous Silica Improves Growth, Water Relations, and Photosynthetic Performance of Sugarcane Under Moderate and Severe Water Deficit - Bezerra, Fabiano Simplicio; do Nascimento, Clístenes Williams Araújo; Gonçalves, Wellinton Julio Ferreira; de Carvalho Leal, Lucas Yago; da Costa Berto, Steffany Daiana; Teixeira, Gelza Carliane Marques; de Mello Prado, Renato [UNESP]; Alves, Deyvielen Maria Ramos [UNESP]; Nunes, José Alfredo; Araújo, Cícero Aparecido Ferreira; Paulino, Martha Katharinne Silva Souza; de Souza, Edivan Rodrigues (Springer Nature, 2025)
The aim of this study was to evaluate the effect of silicon (Si) doses, applied in the form of amorphous silica fertilizer (ASF), in combination with moderate and severe water deficits, on the growth responses, water relations, and photosynthetic performance of sugarcane. The experiment was conducted in a greenhouse environment using a randomized block design in a 2 × 4 factorial arrangement. The treatments comprised two irrigation levels (50 and 20% of crop evapotranspiration – ETc) and four Si doses: 0 (control), 78, 117, and 156 kg ha−1 of Si, which utilized the corresponding doses of 0, 300, 450, and 600 kg ha−1 of amorphous silica-based fertilizer (ASF – 26% Si). Severe water deficit (20% of ETc) significantly restricted sugarcane growth. However, the application of optimal doses of silicon (Si) mitigated these adverse effects by enhancing key physiological mechanisms, including increased relative water content, improved water potential, and better osmotic adjustment. These responses contributed to improved plant growth, as evidenced by increased stalk height, reduced leaf senescence, and a greater number of green leaves. The dose of 78.0 kg ha−1 of Si, equivalent to 300.0 kg ha−1 of ASF, promotes osmotic adjustment in plants under conditions of severe water deficit, showing an increase in the tolerance of sugarcane to water scarcity. For the first time, under moderate and severe water deficit conditions, the potential of FSA to improve growth, water relations and photosynthetic performance of the crop has been demonstrated.